Locational Analysis of Crimes and Its Impact Toward The Housing Prices - Burhan, Burhaida; Chu Yi Ching, (Research in Management of Technology and Business, 2021)
Residential property is a basic need in people’s life and it is very important for humans to have a shelter. In general, crime plays a main role in the health of a city’s housing market. Areas that have low crime rates would enjoy higher property values simply because the buyers are willing to spend for security that they desired. On behalf of that, the objectives of this research are to analyze how the location impacts the crimes and to study the relationship between the location of crime and housing prices. The objectives of this study are achieved by analyzing the transaction data of residential properties provided by the Valuation and Property Services Department (JPPH) and the data of crime rates from Ibu Pejabat Polis Daerah (IPD) Batu Pahat. Hence, the research is focusing on Batu Pahat, Johor. The methodology that will be used in this study is the quantitative technique. The findings of this study revealed that the location that is near to the Central Business District (CBD) will increase the crime rates within the area and the regression analysis shows that there is a positive relationship between the location of crime and the housing prices.